2010
DOI: 10.1021/jf1006209
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Monoclonal Antibody for Melamine and Development of an Indirect Competitive ELISA for Melamine Detection in Raw Milk, Milk Powder, and Animal Feeds

Abstract: Melamine (MEL) has been involved in several food recalls after the discovery of severe kidney damages in children and pets poisoned by melamine-adulterated food. To detect MEL residue in foods and animal feeds, an indirect competitive ELISA (cELISA) method was developed in this study based on preparation of monoclonal antibodies (MAbs) to MEL. The immunogen was prepared by linking MEL hapten with carrier protein via carbodiimide method. The method is applicable in the range of 5.0-135.0 microg L(-1) MEL in buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 17 publications
(18 reference statements)
1
32
0
1
Order By: Relevance
“…Although it is simple, rapid, and economical, some samples still require complicated pretreatment. An alternative method of competitive enzyme-linked immunosorbent assay 26 avoids the complex pretreatment, but needs to be operated by a trained professional. All of these MEL detection methods do not meet the requirements for onsite and in-home testing.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is simple, rapid, and economical, some samples still require complicated pretreatment. An alternative method of competitive enzyme-linked immunosorbent assay 26 avoids the complex pretreatment, but needs to be operated by a trained professional. All of these MEL detection methods do not meet the requirements for onsite and in-home testing.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the sensitive and accurate detection of melamine is of the utmost importance for food safety. Recently, some new technologies, such as high performance liquid chromatography (HPLC) [45], gas chromatography in tandem with mass spectrometry [46] and enzyme-linked immunosorbent assay (ELISA) [47] are employed for the detection of melamine. SERS has emerged as a more rapid and cost-effective method for the identification of adulterants in foods.…”
Section: Resultsmentioning
confidence: 99%
“…ELISA as a screening method now has been developed rapidly (Garber 2008), but false positive results and high LOD weaken its accuracy. Previous publications indicated that the LODs of ELISA were 0.1 mg L À1 in milk, 0.2 mg L À1 in milk powder, 0.5 mg L À1 in feeds (Yin et al 2010) and 20 mg mL À1 in pet-food (Kim et al 2008) for the detection of melamine, respectively. Compared to instrumental methods [LOD, 0.002 mg kg À1 in GC-MS method (Xia et al 2009)], sensitivity of immunoassay still needs to be further improved.…”
Section: Rapid and Sensitive Fluoroimmunoassay Based On Quantum Dots mentioning
confidence: 98%